1998
DOI: 10.1016/s0002-9440(10)65595-2
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Hepatic Parenchymal and Nonparenchymal Cells to Hepatic Fibrogenesis in Biliary Atresia

Abstract: Extrahepatic biliary atresia is a severe neonatal liver disease resulting from a sclerosing cholangiopathy of unknown etiology. Although biliary obstruction may be surgically corrected by a "Kasai" hepatoportoenterostomy , most patients still develop progressive hepatic fibrosis , although the source of increased collagen deposition is unclear. This study examined the role of hepatic stellate cells (HSCs) and assessed the source of transforming growth factor-␤ (TGF-␤) production in hepatic fibrogenesis in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
107
1
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(120 citation statements)
references
References 46 publications
8
107
1
4
Order By: Relevance
“…16 Bound antibody was detected using a biotinylated rabbit anti-goat secondary antibody (Dako, Denmark), followed by streptavidin-peroxidase (StrepABC; Dako) as previously described. 7,8 Negative control used nonimmune anti-human antisera (Dako) in place of primary antibody. Immunohistochemistry was also performed for ␣-smooth muscle actin (␣-SMA) and cytokeratin-7 (CK-7) on human liver sections to assess the role of HSCs and liver progenitor cells, 17 respectively, in MCP-1 expression.…”
Section: Human Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…16 Bound antibody was detected using a biotinylated rabbit anti-goat secondary antibody (Dako, Denmark), followed by streptavidin-peroxidase (StrepABC; Dako) as previously described. 7,8 Negative control used nonimmune anti-human antisera (Dako) in place of primary antibody. Immunohistochemistry was also performed for ␣-smooth muscle actin (␣-SMA) and cytokeratin-7 (CK-7) on human liver sections to assess the role of HSCs and liver progenitor cells, 17 respectively, in MCP-1 expression.…”
Section: Human Studiesmentioning
confidence: 99%
“…We previously demonstrated that activated hepatic stellate cells (HSCs) and periportal myofibroblasts are the principal collagen-producing cells causing cirrhosis in CFLD 7 and BA. 8 It is generally recognized that in normal liver, HSCs exist in a quiescent phenotype in a perisinusoidal location, closely associated with hepatocytes. 9 In liver injury, HSCs are recruited and activated into "myofibroblast-like" cells which have a central role in the deposition of fibrillar collagens and fibrotic matrix and expression of proinflammatory and profibrogenic cytokines and associated receptors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms of increased collagen production and liver parenchyma fibrosis are poorly understood [1,2]. These phenomena are particularly observed in children with biliary obstruction (BO) in whom the evolution to biliary cirrhosis and hepatic failure leads to the need for liver transplantation.…”
mentioning
confidence: 99%
“…To test whether increased HAI-1 or HAI-2 expression plays a role in the fibrosis process in BA livers, portal fibroblasts (PFs) (Fig. 4A) and stellate cells, 20 two major cell types responsible for cholestasis-related fibrosis, 29,30 were treated with conditioned media from Hep3B cells stably overexpressing HAI-1 or HAI-2 (Fig. 4B) or control media (green fluorescent protein [GFP] or vector) to assay their effects on the fibrogenic activity.…”
Section: Resultsmentioning
confidence: 99%